"A Love Story Pure and Simple": Harper Lee and Atticus Finch. Issue 1 (1st January 2018) - Epperson, Hannah
ABSTRACT: The article explores the evolution of the character Atticus Finch from Harper Lee's Pulitzer Prize–winning novel, To Kill a Mockingbird, to the recently released Go Set a Watchman . The enduring popularity of To Kill a Mockingbird and iconic status of Atticus Finch as a champion of justice and racial equality made the publication of Go Set a Watchman and character reversal of Atticus Finch a shock to the literary world, with reverberations into popular American culture. Through an examination of Lee's writing process, the circumstances of each novel's publication, and the influence of Lee's editor and father, this article reveals how Atticus Finch seemingly transformed from a lawyer-hero to an aging racist.